A Demonstration of the Uncertainty in Predicting the Estrogenic Activity of Individual Chemicals and Mixtures From an In Vitro Estrogen Receptor Transcriptional Activation Assay (T47D-KBluc) to the In Vivo Uterotrophic Assay Using Oral Exposure. (29th July 2016) - Conley, Justin M.; Hannas, Bethany R.; Furr, Johnathan R.; Wilson, Vickie S.; Gray, L. Earl
Abstract: In vitro estrogen receptor assays are valuable tools for identifying environmental samples and chemicals that display estrogenic activity. However, in vitro potency cannot necessarily be extrapolated to estimates of in vivo potency because in vitro assays are currently unable to fully account for absorption, distribution, metabolism, and excretion. To explore this issue, we calculated relative potency factors (RPF), using 17α-ethinyl estradiol (EE2) as the reference compound, for several chemicals and mixtures in the T47D-KBluc estrogen receptor transactivation assay. In vitro RPFs were used to predict rat oral uterotrophic assay responses for these chemicals and mixtures. EE2, 17β-estradiol (E2), benzyl-butyl phthalate (BBP), bisphenol-A (BPA), bisphenol-AF (BPAF), bisphenol-C (BPC), bisphenol-S (BPS), and methoxychlor (MET) were tested individually, while BPS + MET, BPAF + MET, and BPAF + BPC + BPS + EE2 + MET were tested as equipotent mixtures. In vivo ED50 values for BPA, BPAF, and BPC were accurately predicted using in vitro data; however, E2 was less potent than predicted, BBP was a false positive, and BPS and MET were 76.6 and 368.3-fold more active in vivo than predicted from the in vitro potency, respectively. Further, mixture ED50 values were more accurately predicted by the dose addition model using individual chemical in vivo uterotrophic data (0.7-1.5-fold difference from observed) than in vitro data (1.4-86.8-fold). Overall, these data illustrate the potential for both underestimating and overestimating in vivo potency from predictions made with in vitro data for compounds that undergo substantial disposition following oral administration. Accounting for aspects of toxicokinetics, notably metabolism, in in vitro models will be necessary for accurate in vitro -to- in vivo extrapolations.